Medicinal Plants Used by the Vantangiya Tribe of North-Eastern Terai Region, Uttar Pradesh, India - Srivastava, Deepa; Rauniyar, Neha; Mishra, Manisha (Pharmacognosy Communications)
The present study was undertaken to collect information from local tribe Vantangiya about their traditional healers based on medicinal plants and their uses during August 2019-till date. Five villages where the Vantangiya tribal community have been residing since 1922, have been selected for the purpose. The selected villages are Jangal Tinkoniya, Khale Tola, Aambagh, Rajahayi and Chilbilva, located at around 50 Km-70 Km from Gorakhpur city and spread over around 110 hectares. The indigenous knowledge was gathered through interactions and questionaries with residing tribals and their traditional healers. The study sheds knowledge on around thirty species belonging to different families. The various medicinal plant parts used were bark, flowers, rhizomes, roots, leaves, seeds, gum and sometimes whole plants. These are effective against skin, respiratory, cardiovascular, gastrointestinal, gynaecological disorders, Jaundice, ophthalmic infection, and snakebite etc. Despite urbanisation, the rural folk and the tribal of the district still hold their traditional faith and depend on indigenous plants for their various needs, especially as medicines. Although the Vantangiya tribe has been preserving their traditional knowledge, there is insensitivity among the youngsters for this wealth of knowledge, and the uses of these herbal plants is expected to dwindle in the future. To pass on the expertise of the Vantangiya tribe about these plants and their efficacy in curing diseases, they should be conserved for sustainability of resources to our future generation.
Keywords: Ethnomedicine; Medicinal plants; Pathological disorders; Tribal community; Vantangiya tribe